(untitled) (Fiep Bulletin - online, 2011)
Basketball is an sport of long duration and moderate intensity, because of those aspects it demands a lot from it’s participants. The main goal of these study is to prove the importance of basketball in schools seeking the development of the agility in students of a public school in the city of Guarapuava – Paraná. 62 ( sixty two) children (male and female) from two classes randomly picked, were put to a agility test, shuttle run, in the first moment the students performed an pilot test, and, in the second moment the real test. The students were separated in two groups, group A, participated in the basketball classes, and group B, the control group, that participated in the normal classes, following the curricular planning. Both groups were submitted to the previously mentioned planning and rated again at the end of the classes. All the results were analyzed through averaged and standard deviation, the ANOVA one-way was used, with a significance level of 5%(p≤0.05) to compare all data, being all result normalized and shown in tables and graphics. It is understood, that both groups, basketball and control, didn`t shown a significant improvement in the shuttle run test when applied to children under the circumstances previously showed, at a public school in Guarapuava - PR.